Trimethyl borate as an electrolyte additive for high potential layered cathode with concurrent improvement of rate capability and cyclic stability. (1st December 2015) - Wang, Zaisheng; Xing, Lidan; Li, Jianhui; Li, Bin; Xu, Mengqing; Liao, Yuhao; Li, Weishan
Abstract: Trimethyl borate (TB) is used as an electrolyte additive to improve cyclic stability and rate capability of a layered cathode, LiNi1/3 Co1/3 Mn1/3 O2 (LNCM), under 4.5 V (vs. Li/Li + ). Charge/discharge tests demonstrate that the cyclic stability and rate capability of LNCM can be improved significantly by adding TB into a standard (STD) electrolyte, 1.0 mol L −1 LiPF6 in ethylene carbonate/ethyl methyl carbonate/diethyl carbonate (3/5/2, in weight). After 200 cycles at 0.5C between 3.0 and 4.5 V, LNCM exhibits a capacity retention of 89% in 10% TB-containing electrolyte, but only 48% in STD electrolyte. Unlike other additives, which usually decrease the rate capability when they are used for the cyclic stability improvement of LNCM, the discharge capacity of LNCM at 6C is enhanced from 78 mAh g −1 in STD electrolyte to 102 mAh g −1 in 10% TB-containing electrolyte. Physical and electrochemical characterizations demonstrate that these improvements result from the preferential oxidation of TB compared to the STD electrolyte and the formation of a stable and low impedance film on LNCM cathode surface, which suppresses concurrently the decomposition of electrolyte and the dissolution of transition metal ions from LNCM.